Multiple exposure pathways and health risk assessment of heavy metal(loid)s for children living in fourth-tier cities in Hubei Province - Zhang, Hongxing; Mao, Zhenxing; Huang, Kai; Wang, Xiu; Cheng, Ling; Zeng, Lingshuai; Zhou, Yikai; Jing, Tao (Environment international, 2019)
In the past, most research focused on the children living near a typical contaminated area but ignored the health risks of children living in the fourth or fifth tier cities without typical contaminated sources. These cities are now facing a series of problems, such as serious environmental pollution, undeveloped health system and so on. Furthermore, the development of modern logistics for food delivery has altered lifestyles that directly impact diets and eating patterns. In this study, multiple exposure pathways and health risks of children to heavy metal(loid)s were studied based on questionnaire-based surveys and field sampling of soil, dust, fine particulates, drinking water and food. We found that Pb, Cd and Mn levels in environmental samples were very high indicating a serious pollution problem. Inhalation exposure via aerosol particles was the most important pathway and was greater than exposure by food ingestion. The hazard index for Mn via aerosol particles was >1 even at the 5th percentile and Mn levels in urine was 10 times higher than those of people living in typical contaminated areas. The total incremental lifetime cancer risk (ILCR) for all metal(loid)s was also higher than the threshold at the 95th percentile. This study highlights health risks to children living in fourth tier cities and the importance of air pollution control to protect heavy metal exposure for children. •Multiple exposure pathways and health risks of children are analyzed.•Inhalation exposure via aerosol particles has become the main exposure pathway.•Metals in food were low, which were only one-tenth of previously reported values.•The local Mn pollution most likely contributes to high environmental exposure.•High health risks happen to the local children living in fourth-tier cities.